Influence of different thickness of sheet standards is for tests on stretch on surface of maximum deformations. - Писаренко, В.Г.; Савуляк, В.В.; Билічкіна, В.Є. (Problems of Tribology, 2015)
In the article influence of geometrical descriptions of sheet standards is analysed on indexes tensely deformed to consisting of area of measuring during tests on a stretch. It is set that on heterogeneity of size of indexes of the tense consisting of area of measuring during tests on a stretch the different thickness of letter has a most influence. Certainly size of rejections of indexes of the tense state from the geometrical parameters of letter.